TAX ACCOUNTING: BIBLIOMETRIC STUDY OF THE ACCOUNTING AREA BETWEEN THE PERIOD 2010 TO 2020 - Henrique, Marcelo Rabelo; da Silva, Jéssica Medeiros; Saporito, Antonio; Silva, Sandro Braz (RC&C: Revista de Contabilidade e Controladoria, 2021)
The present study aimed to investigate how the scientific production on “Tax Accounting” is characterized in the magazines Contabilidade Vista & Revista and in the Revista Brasileira de Gestão e Negócios - RBGN between the period of 2010 to 2020. In order to carry out the exposed objective, we adopted if the bibliometric approach, the bibliometric measurement technique was adopted through methodologies based on the Bradford Laws (productivity of journals) and Lotka Laws (productivity of the authors) which aims to find the frequency of certain terms in a scientific article. The results showed that there are more empirical than theoretical articles, two to four authors per publication are common, the most common academic degree of the authors is a master's / master's degree, authors graduated from Universities in the Southeast and South regions made the greatest contributions, there is a preference in references for articles. It was also possible to obtain characteristics of the publications on Tax Accounting and by means of a small sample of articles published with this theme, to infer several relevant information. In order to add to the scientific production, on this branch that presents itself infrequently in relation to research in the Accounting area.